Positive Reinforcement Assistance on the Effectiveness of Volleyball Forearm Passing Learning - Deddy Whinata Kardiyanto; Andri Asrul Setiyawan; Wildan Arya Kusuma; Prayogi Dwina Angga (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
In addition to improving motivation and self-confidence, the positive reinforcement–based mentoring activities also brought significant changes to the learning dynamics in the field. Students who were previously passive and hesitant began to show greater confidence when attempting the forearm passing technique. Each form of praise and feedback provided encouraged students to repeat the movement with increased assurance. This was evident from the growing number of students who voluntarily stepped forward to practice the technique in front of the group. Positive changes were also observed in the quality of interaction between students and lecturers. The reinforcement approach created a more dialogic and supportive learning atmosphere. Students felt appreciated, making them more receptive to corrections and more responsive in improving their technical errors. The training environment became more conducive and collaborative, as students supported one another whenever progress was demonstrated by their peers. Furthermore, observational results indicated a significant improvement in the students’ forearm passing accuracy, particularly in body positioning, arm swing, and movement coordination. This improvement was not only seen in students who initially displayed adequate skills but also in those who previously faced limitations. This demonstrates that the implementation of reinforcement has an equal and inclusive effect on all participants. Students also expressed that this approach made them feel more comfortable and motivated throughout the learning process. They perceived positive reinforcement as providing psychological safety, as mistakes were not regarded as failures but as essential elements of the learning process. This condition fostered a more humanistic learning climate and encouraged students to continually engage in self-improvement. Thus, the outcomes of this community service program not only enhanced students’ technical skills but also developed a more positive, supportive, and sustainable learning culture. This mentoring model has the potential to be applied to other volleyball techniques as well as to other sports-related courses that require a motivational approach